2020
DOI: 10.1186/s12963-020-00222-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between firearms and mortality in Brazil, 1990 to 2017: a global burden of disease Brazil study

Abstract: Background Brazil leads the world in number of firearm deaths and ranks sixth by country in rate of firearm deaths per 100,000 people. This study aims to analyze trends in and burden of mortality by firearms, according to age and sex, for Brazil, and the association between these deaths and indicators of possession and carrying of weapons using data from the global burden of diseases, injuries, and risk factors study (GBD) 2017. Methods We used GBD 2017 estimates of mortality due to physical violence and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
(51 reference statements)
1
10
0
5
Order By: Relevance
“…Likewise, Pará, Maranhão, and Bahia had the largest increases in firearm prevalence and were also among the few states that showed increased firearm-specific suicide rates [ 25 ]. In line with these findings, a study using data from the Global Burden of Disease study showed that rates of firearm-related deaths are associated with the numbers of firearms voluntarily returned following implementation of the Disarmament Statute; while rates of firearm-related deaths tended to increase between 2000 and 2017 in states with low numbers returned, states with the highest numbers of firearms returned showed reductions in the rates of firearm-related deaths [ 6 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Likewise, Pará, Maranhão, and Bahia had the largest increases in firearm prevalence and were also among the few states that showed increased firearm-specific suicide rates [ 25 ]. In line with these findings, a study using data from the Global Burden of Disease study showed that rates of firearm-related deaths are associated with the numbers of firearms voluntarily returned following implementation of the Disarmament Statute; while rates of firearm-related deaths tended to increase between 2000 and 2017 in states with low numbers returned, states with the highest numbers of firearms returned showed reductions in the rates of firearm-related deaths [ 6 ].…”
Section: Discussionmentioning
confidence: 92%
“…The total rate of death by firearms in Brazil is among the highest in the world, accounting for 21.5 deaths per 100,000 Brazilians in 2017 [ 6 ]. Ready access to firearms, whether legal or illegal, arguably facilitates deaths by firearms, including suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in Brazil's domestically produced weapons have correlated with increases in firearm violence. 6,7 Despite these trends, the firearm industry in Brazil argues that the increase in violence is due to "imported" small arms to influence policy decisions and continues with their local production. 7 As the United States is also a large importer of weapons from Brazil, their extensive supply chains ensure that production and profits in Brazil remain high.…”
Section: Private Industry's Role In Firearm Violencementioning
confidence: 99%
“…Introdução O suicídio de idosos, pessoas com 60 anos ou mais, é considerado pela Organização Mundial da Saúde como um dos mais graves problemas de saúde pública, pois o risco aumenta com a idade [1][2][3][4][5][6][7][8][9] e essa é a população em maior crescimento [7].…”
unclassified
“…No Brasil, o aumento da longevidade tem modificado a estrutura demográfica de forma distinta em cada região; com o registro dos maiores índices de envelhecimento no estado do Rio Grande do Sul (RS) [3,6,10,11] e, dentre as capitais, em Porto Alegre [12][13].…”
unclassified